The Role of Experience and Gender in Founders' Business Planning Activities: A Meta Analysis - Ma, Jiangshui; Chen, Shuxing; Wu, Yenchun Jim; Shu, Min (Frontiers in Psychology, 2021)
The question of why entrepreneurs undertake business planning activities differently, ranging from planning “in the head” to generating formal written documents, is still impenetrable. By aggregating data on 11064 observations from 32 independent data set, this study meta-analyzed how business experience and gender influence entrepreneurs’ disposition to business planning behaviors. Surprisingly, contradictory to some extant views that entrepreneurs with prior experience are less likely to make business plans, we found that both managerial experience and entrepreneurial experience positively influence entrepreneurs’ subsequent business planning behaviors. Drawing insight from the effectuation and institutional perspectives, this study showed that, rather than entrepreneurial experience, managerial experience motivates entrepreneurs to generate formal business plans. For entrepreneurs who create formal business plans, both entrepreneurial experience and managerial experience enhance their business planning sophistication. In addition, we examined the moderating effects of gender on the relationship between business experience and business planning. The results suggested that female entrepreneurs with entrepreneurial experience are more likely to undertake business planning behaviors and create formal business plans than their male counterparts.